PENGEMBANGAN BANDPASS FILTER KOMPOSIT PITA SANGAT LEBAR BERBASIS TEKNOLOGI MIKROSTRIP - Achmad Munir; Ivan Pradibta; Zainal Abidin (SENTIA 2016, 2016)
This paper discusses the development of microstrip-based ultra-wideband (UWB) composite bandpass filter (BPF) with stubs. The BPF is compositely constructed from the step impedance lowpass filter (LPF) and the optimum distributed highpass filter (HPF). Prior to the realization, the performances of filter and its physical dimension are investigated numerically to obtain the optimum design. The composite BPF is deployed on an FR4 Epoxy dielectric substrate with the thickness of 0.8mm and the dimension of 30mm x 25mm. From the measurement result, it shows that the realized UWB composite BPF has -3dB bandwidth response of 9.33GHz ranges from the frequency of 1.67GHz to 11GHz.